2014
DOI: 10.1017/s0021859614000458
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients released during the decomposition of pruning residues used as plant cover and their effect on soil fertility

Abstract: SUMMARYThe arrival on the market of various types of mulchers and chippers has boosted the use of pruning residues as plant cover among olive growers. In order to increase knowledge regarding the decomposition of these types of residues and their effect on soil fertility, an experiment was performed using different doses and sizes of pruning residues applied on the areas between the lines of olive trees in an organic olive grove.Experiments were conducted over a period of two growing seasons (2009/10 and 2010/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For example, non-structural elements such as K are rapidly lost from the organic material when the cell wall breaks down during decomposition and soluble P containing compounds are easily leached during decomposition compared to N which participates in the structural section of organic compounds; hence, it is slowly released during decomposition (Issac and Nair 2005;Hossain et al 2011;Dawoe et al 2010;Naik et al 2018). Ordóñez-Fernández et al (2015) indicated that K is highly soluble and mobile, that implies environmental conditions such as soil moisture or rainfall may possibly accelerate its release from decomposing matter compared to other nutrients. Additionally, preferential retention of N by microbes while K or P is being rapidly released from the substrate may account for the faster release of P and K than N (Singh and Sherhar 1989).…”
Section: Nutrient Release Dynamicsmentioning
confidence: 99%
“…For example, non-structural elements such as K are rapidly lost from the organic material when the cell wall breaks down during decomposition and soluble P containing compounds are easily leached during decomposition compared to N which participates in the structural section of organic compounds; hence, it is slowly released during decomposition (Issac and Nair 2005;Hossain et al 2011;Dawoe et al 2010;Naik et al 2018). Ordóñez-Fernández et al (2015) indicated that K is highly soluble and mobile, that implies environmental conditions such as soil moisture or rainfall may possibly accelerate its release from decomposing matter compared to other nutrients. Additionally, preferential retention of N by microbes while K or P is being rapidly released from the substrate may account for the faster release of P and K than N (Singh and Sherhar 1989).…”
Section: Nutrient Release Dynamicsmentioning
confidence: 99%
“…Nevertheless, most olive growers use spontaneous vegetation due to economic savings in seed. In 2018, 92% of the Spanish olive grove areas with any type of CC had a spontaneous CC [16] that was occasionally combined with mulch cover of pruning residues, which are durable, protect the soil and enhance soil fertility [17][18][19][20]. However, the continued use of the same CC produces a change in ruderal flora.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Parras‐Alcántara et al () also observed that pruning residues used as a mulch can improve soil physical and chemical properties in olive groves. Likewise, Ordóñez‐Fernández et al () found an increase in the soil contents of N, P and K following the application of this kind of residues. Indeed, farmers are increasingly adopting chopped pruning as mulch (Calatrava & Franco, ).…”
Section: Introductionmentioning
confidence: 84%
“…The decomposition of pruning residues is a complex process (Ordóñez-Fernández et al, 2015). The size of the remains affects the specific surface in contact with the ground and therefore its microbial colonization.…”
Section: Introductionmentioning
confidence: 99%